Distribution of class ii major histocompatibility complex antigenexpressing cells in human dental pulp with carious lesions - Tetiana Haniastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Dental caries is a bacterial infection which causes destruction of the hard tissues of the tooth. Exposure of the dentin to the oral environment as a result of caries inevitably results in a cellular response in the pulp. The major histocompatibility complex (MHC) is a group of genes that code for cell-surface histocompatibility antigens. Cells expressing class II MHC molecules participate in the initial recognition and the processing of antigenic substances to serve as antigen-presenting cells. Purpose: The aim of the study was to elucidate the alteration in the distribution of class II MHC antigen-expressing cells in human dental pulp as carious lesions progressed toward the pulp. Methods: Fifteen third molars with caries at the occlusal site at various stages of decay and 5 intact third molars were extracted and used in this study. Before decalcifying with 10% EDTA solution (pH 7.4), all the samples were observed by micro-computed tomography to confirm the lesion condition three-dimensionally. The specimens were then processed for cryosection and immunohistochemistry using an anti-MHC class II monoclonal antibody. Results: Class II MHC antigen-expressing cells were found both in normal and carious specimens. In normal tooth, the class II MHC-immunopositive cells were observed mainly at the periphery of the pulp tissue. In teeth with caries, class II MHC-immunopositive cells were located predominantly subjacent to the carious lesions. As the caries progressed, the number of class II MHC antigen-expressing cells was increased. Conclusion: The depth of carious lesions affects the distribution of class II MHC antigen-expressing cells in the dental pulp.Latar belakang: Karies merupakan penyakit infeksi bakteri yang mengakibatkan destruksi jaringan keras gigi. Dentin yang terbuka akibat karies akan menginduksi respon imun seluler pada pulpa. Kompleks histokompatibilitas utama (MHC) merupakan sekumpulan gen yang mengkode histokompatibilitas antigen-antigen permukaan sel. Sel-sel yang mengekspresikan molekul-molekul ini berpartisipasi dalam pengenalan awal substansi-substansi antigenik untuk selanjutnya diproses dan dipresentasikan pada permukaan sel. Tujuan: Penelitian ini bertujuan untuk mengetahui perubahan distribusi sel-sel yang mengekspresikan molekul MHC kelas II pada pulpa gigi manusia dengan meningkatnya keparahan karies. Metode: Penelitian ini menggunakan 15 gigi molar ketiga yang mengalami karies pada permukaan oklusal dengan berbagai tingkat kedalaman dan 5 gigi molar ketiga normal (tidak mengalami karies). Sebelum didekalsifikasi dengan larutan EDTA 10% (pH 7,4), seluruh sampel diamati dengan menggunakan micro-computed tomography untuk mengetahui kedalaman lesi karies secara tiga dimensi. Spesimen kemudian diproses untuk dilakukan cryosection dan dilakukan immunohistokimia dengan menggunakan monoklonal antibodi anti MHC kelas II. Hasil: Ekspresi MHC kelas II oleh sel-sel pada ruang pulpa dijumpai disemua spesimen baik pada kondisi normal maupun karies. Pada gigi normal, sel-sel yang mengekspresikan MHC kelas II terletak terutama pada tepi pulpa. Pada gigi-geligi yang mengalami karies, agregasi sel-sel yang mengekspresikan MHC kelas II terutama terletak di bawah lesi karies. Semakin dalam lesi karies, jumlah sel-sel yang mengekspresikan MHC kelas II semakin meningkat. Kesimpulan: Kedalaman lesi karies berpengaruh terhadap distribusi sel-sel yang mengekspresikan MHC kelas II pada pulpa.